Utvärdering av systemprestanda och tillförlitlighet genom en simulerad operativ miljö med en poängbaserad modell - Nilsson Lundqvist,Benjamin; Strand,Jesper (CODEN:LUTEDX/TEIE, 2023)
The thesis focuses on the evaluation and testing of FLEXNET, an Unattended Ground Sensor (UGS) system developed by Bertin Exensor. The primary purpose of FLEXNET is to monitor large areas without requiring extensive resources in the form of personnel actively monitoring and maintaining the system on site. In the development of comprehensive systems it can often be challenging to carry out full-scale tests of the entire system within the confines of a company's own premises. Currently for more extensive tests the company has been forced to set up the entire system in the field. This has proven to be very resource-intensive, and the parameters of the environment can vary from day to day. Therefore, this thesis, in consultation with the company, explores and implements the possibility of testing a complete system using a Raspberry Pi and Python to simulate an operational environment for the system inside the office. The goal of the thesis is to develop a reliable and comprehensive test rig that makes it easier for employees to continuously test their products without having to leave the office. The development process was carried out in several stages. Initially, the thesis workers explored methods for physically connecting to the devices. Subsequently, sensor data was generated for the sensors to evaluate whether it resulted in an adequate alarm signal. Finally, several sensors were fed data simultaneously to analyze the overall system's interactions. The results from the thesis indicate that it is possible to use a Raspberry Pi to simulate an operational environment for the system within the office setting. Additionally, it provides and scores valuable information about the system's performance using statistical modeling.
Keywords: Systemtestning; Seriell kommunikation; Python; Elektronik; Automation